2017
DOI: 10.1123/jab.2015-0329
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Running Ground Reaction Force Parameters from Motion Analysis

Abstract: We compared running mechanics parameters determined from ground reaction force (GRF) measurements with estimated forces obtained from double differentiation of kinematic (K) data from motion analysis in a broad spectrum of running speeds (1.94-5.56 m⋅s). Data were collected through a force-instrumented treadmill and compared at different sampling frequencies (900 and 300 Hz for GRF, 300 and 100 Hz for K). Vertical force peak, shape, and impulse were similar between K methods and GRF. Contact time, flight time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
6
14
0
2
Order By: Relevance
“…Estimated GRF results in this study are comparable to other laboratory-based studies aiming to predict 208 GRF from marker trajectory data using a mechanical approach. The impulse errors for low-speed 209 running (2.3%), impact peak errors for moderate-speed running (9.2%) and correlations between 210 estimated and measured impact peaks for low-to high-speed running (R 2 =0.77-0.96) found in the current study are similar to results reported in previous studies that aimed to predict GRF from marker 212 trajectory data for comparable constant speed running tasks 25, 26,31 . However, this study extends 213 beyond other studies in that similar results were also achieved for a range of high-intensity and 214 dynamic running tasks frequently undertaken in running-based sports.…”
Section: Discussion 192supporting
confidence: 84%
See 2 more Smart Citations
“…Estimated GRF results in this study are comparable to other laboratory-based studies aiming to predict 208 GRF from marker trajectory data using a mechanical approach. The impulse errors for low-speed 209 running (2.3%), impact peak errors for moderate-speed running (9.2%) and correlations between 210 estimated and measured impact peaks for low-to high-speed running (R 2 =0.77-0.96) found in the current study are similar to results reported in previous studies that aimed to predict GRF from marker 212 trajectory data for comparable constant speed running tasks 25, 26,31 . However, this study extends 213 beyond other studies in that similar results were also achieved for a range of high-intensity and 214 dynamic running tasks frequently undertaken in running-based sports.…”
Section: Discussion 192supporting
confidence: 84%
“…However, this study extends 213 beyond other studies in that similar results were also achieved for a range of high-intensity and 214 dynamic running tasks frequently undertaken in running-based sports. Moreover, previous studies 215 failed to include the mediolateral and anteroposterior components of acceleration and GRF 25,31 , 216 utilised small sample sizes 25,26,31 and/or investigated running on a treadmill rather than overground 217 26,31 , all of which limit their ability to translate their findings from the lab to an applied sport setting. 218…”
Section: Discussion 192mentioning
confidence: 99%
See 1 more Smart Citation
“…Their results are similar to those reported in the present study. Thus, inverse and forward dynamics, which often differ in their prediction in constant speed running 27,31 because of a bias localization of BCoM of the former methodology, concur to reveal the same dynamics in the acceleration phase of a sprint. As inverse dynamics is unable to account for the visceral mass oscillation in affecting BCoM position, 32,33 the similar mechanical results obtained by means of the methods suggests that visceral mass vertical oscillation excursion is decreased in the acceleration phase of sprint running due to a diminished "bounciness" of the spring-mass system.…”
Section: Discussionmentioning
confidence: 88%
“…However, none of the aforementioned approaches provided users with kinetic information. Efforts to move kinetic analyses out of the laboratory setting have proven to be effective for trunk bending (Faber et al, 2016 ), gait (Karatsidis et al, 2017 ), dance (Shippen and May, 2012 ), and running (Pavei et al, 2017 ). However, aforementioned approaches require full-body kinematic information.…”
Section: Introductionmentioning
confidence: 99%